Utilization of Azolla nilotica in lumpiang shanghai (Journal of the Philippine Association for Technology in Home Economics in State Colleges and Universities, Inc., 2000)
Azolla nilotica was used in varying proportions, from 25%, 50%, 75%, to 100% as replacement for meat in preparing lumpiang shanghai (meat rolls). Utilizing 25% to 75% Azolla nilotica as a substitute for meat in shanghai rolls had statistically comparable general acceptability to that of 100 percent meat. All of the samples had varied levels of general acceptability among the consumers in all the three trials conducted. Shanghai meat roll with 100 percent meat was still ranked as number 1, the highest, which was liked extremely. Shanghai meat rolls with 25% azolla was ranked second which was liked very much. Shanghai meat rolls with 50 percent and 75 percent azolla ranked third and fourth were liked moderately and slightly, respectively. Shanghai meat rolls with 100% azolla ranked fifth which was neither like nor disliked.